2016
DOI: 10.1111/jdv.13622
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, randomized, single‐blind comparison of topical clindamycin 1%/benzoyl peroxide 5% once‐daily gel versus clindamycin 1% twice‐daily gel in the treatment of mild to moderate acne vulgaris in Chinese patients

Abstract: NCT01915732.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Among 2461 potential studies, 206 satisfied the inclusion criteria (eFigure in the Supplement). Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 2461 potential studies, 206 satisfied the inclusion criteria (eFigure in the Supplement). Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
“… Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Xu et al also found CDP 1%/BPO 5% to be superior to clindamycin 1% gel monotherapy in a single-blind randomized comparison trial of 1016 subjects with mild-to-moderate acne over 12 weeks. 20 More recently, a gel formulation containing CDP 1.2%/BPO 3.75% was developed. Pariser et al investigated the efficacy of once-daily CDP 1.2%/BPO 3.75% in 498 subjects with moderateto-severe acne over 12 weeks compared to vehicle.…”
Section: Bpo-clindamycin Combinationsmentioning
confidence: 99%
“…Even though some of them are used in monotherapy, the advantage of various combinations of the above-mentioned substances in therapy has shown superior effects in many studies and is included in European guidelines [7,10,11]. What is more, many research studies indicate that agents such as topical antibiotics should not be used in monotherapy because of growing bacterial resistance and the limited action of such treatment [12,13].…”
Section: Topical Treatmentmentioning
confidence: 99%